Pelaksanaan Evaluasi Pembelajaran Akidah Akhlak Di MtsN 13 Tanah Datar - Indung Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
This research is motivated. 20 of 2003 article 597 paragraph 1 explains that the evaluation of students is carried out by educators to monitor the process, progress, and improvement of student learning outcomes on an ongoing basis. Therefore, researchers are interested in researching this because in the learning process the teacher must carry out formative assessment as stated in the lesson plan but in practice the teacher does not apply it. This type of research is a field research and is descriptive analysis. The approach used is a qualitative method. This study describes how the evaluation of moral aqidah learning at MTsN 13 Tanah Datar is carried out. Data collection techniques are observation, interviews, and documentation. Based on the results of the study, it was shown that the evaluation of moral aqidah learning at MTsN 13 Tanah Datar had been carried out but not optimally. This can be seen from the main steps that must be taken in evaluation activities, the teacher carries out the steps, namely making plans which include assessment objectives, identifying and learning outcomes, compiling grids, developing draft instruments, testing and analyzing instruments, revising and compile a new instrument, the implementation of evaluation is how the teacher carries out an evaluation with evaluation planning. In carrying out the evaluation, it really depends on the type of evaluation used.